2020
DOI: 10.21203/rs.3.rs-26027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Stellate Ganglion Block on Postoperative Recovery of Gastrointestinal Function in Patients Undergoing Surgery with General Anaesthesia: A Meta-Analysis.

Abstract: Background: The return of normal gastrointestinal function is an important signal of postoperative recovery in patients undergoing surgery with general anaesthesia, especially for abdominal surgery. Current methods to resolve this problem are conservative, and the effects are sometimes limited. We aimed to summarize the effects of stellate ganglion block(SGB) on the recovery of gastrointestinal function to explore methods for anaesthesiologists to contribute to postoperative patient recovery. RuMethods: Select… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was confirmed by pathological examination as primary hepatocellular carcinoma. (ii) All patients met the surgical indications [8] and had not undergone minimally invasive treatment or biological treatment for hepatocellular carcinoma before enrollment. (iii) All patients were first-time patients; all signed the informed consent form.…”
Section: Inclusion Criteria (I)mentioning
confidence: 99%
“…It was confirmed by pathological examination as primary hepatocellular carcinoma. (ii) All patients met the surgical indications [8] and had not undergone minimally invasive treatment or biological treatment for hepatocellular carcinoma before enrollment. (iii) All patients were first-time patients; all signed the informed consent form.…”
Section: Inclusion Criteria (I)mentioning
confidence: 99%
“…Early return of gastrointestinal function facilitates postoperative recovery of patients under general anesthesia. SGB can inhibit the excitation of the sympathetic nervous system, thereby restoring the balance of the autonomic nervous system and rebuilding the homeostasis of the neuroendocrine-immune system [32]. Furthermore, Zhao et al reported that SGB relieved symptoms of chronic ulcerative colitis [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment, we observed the loop blood ow of rats after hemorrhagic shock and found that the intestinal perfusion in the Shock group was signi cantly reduced, but the intervention of SGB signi cantly increased the intestinal blood ow in the Shock group. A recent systematic review and meta-analysis of the effect of SGB on the recovery of gastrointestinal function in patients undergoing general anesthesia con rmed the effect of SGB in promoting gastrointestinal recovery after traumatic surgery, which was related to gastrointestinal blood vessels telangiectasis and gastrointestinal motility improvement through the blockage of sympathetic nerves that innervate the gastrointestinal system [23] . The present result suggests that SGB postprocessing improves the intestinal blood supply after hemorrhagic shock, which is bene cial for reducing intestinal damage.…”
Section: Discussionmentioning
confidence: 99%